The Role of Motivation and Work Discipline on Employee Performance in the Operator Section At PT. Sigma Mitra Sejati Cilegon - Saleh, Muhammad; Sunardi, Sunardi; Hartoko, Gatot; Shella , Nurul; Listiawati, Listiawati (Bina Bangsa International Journal of Business and Management, 2021)
This study aims to determine the role of motivation and work discipline on the performance of production operator employees at PT. Sigma Mitra Sejati Cilegon City. The method used in this research is the associative descriptive method. Data analysis techniques used include Normality Test, Classical Assumption Test, Determination Test and Hypothesis Testing. This study indicates that motivation has a significant effect on performance, work discipline has a substantial impact on performance, and motivation and work discipline substantially impact performance